Development of wide area protection for electrical distribution system in Vientiane Capital - A. Philavong (2018)
© 2017 IEEE. This paper presents the development of wide area protection (WAP). The studied case focuses on Vientiane Capital area, Lao PDR. It consists seven substations which are connected the loop network in 22 kV distribution system. The protection system based a characteristic are setting on substation each. The fault area in circuit mainly was affecting the operation of protection, when has occurred a fault in the system. It is a result of the protection setting may not coordinate in all happened situations. Therefore, the wide area protection needs to be considered in especially the big city. The objective of research considered the protection problem in the loop model network also focus on the problem from contingency event and setting a not coordination of overcurrent (OC) relay. So, the operating time of the protective devices needs to set proper with operating of OC relays, which will protect the outage electricity on a wide area. However, these problems will be corrected by finding the method for the setting in the coordinating time interval (CTI) and together with conditional in the contingency analysis. A DIgSILENT Power Factory software will be used in the paper by analyzing the system. The result shows the suitability of the coordination time in the protection system together with an analysis of the contingency condition.